Gingerbread baby - Brett, Jan, 1949-; Hearne, Joseph (New York : G.P. Putnam's, 1999)
A young boy and his mother bake a gingerbread baby that escapes from their oven and leads a crowd on a chase similar to the one in the familiar tale about a not-so-clever gingerbread man.
3.0
K-3
K-3
Wilson's Children
School Library Journal
Publisher's Weekly
Keywords: Gingerbread -- Fiction; Baking -- Fiction; Gingerbread -- Folklore; Baking -- Fiction